Human gut, breast, and oral microbiome in breast cancer: A systematic review and meta-analysis - Thu, May Soe; Chotirosniramit, Korn; Nopsopon, Tanawin; Hirankarn, Nattiya; Pongpirul, Krit (Frontiers in Oncology, 2023)
Introduction: Dysbiosis characterises breast cancer through direct or indirect interference in a variety of biological pathways, therefore, specific microbial patterns and diversity may be a biomarker for the diagnosis and prognosis of breast cancer. However, there is still much to determine about the complex interplay of the gut microbiome and breast cancer. Objective: To evaluate microbial alteration in breast cancer patients compared to control subjects, to explore intestine microbial modification from a range of different breast cancer treatments, and to identify the impact of microbiome patterns on the same treatment-receiving breast cancer patients. Results: A total of 33 articles from 32 studies were included in the review, representing 19 case-control, 8 cohort, and 5 nonrandomised intervention researches. The gut and breast bacterial species were elevated in the cases of breast tumours, a significant increase in Methylobacterium radiotolerans (p = 0.015), in compared to healthy breast tissue. Meta-analysis of different α-diversity indexes such as Shannon index (p = 0.0005), observed species (p = 0.006), and faint's phylogenetic diversity (p < 0.00001) revealed the low intestinal microbial diversity in patients with breast cancer. The microbiota abundance pattern was identified in different sample types, detection methods, menopausal status, nationality, obesity, sleep quality, and several interventions using qualitative analysis. Conclusions: This systematic review elucidates the complex network of the microbiome, breast cancer, and therapeutic options, with the objective of providing a link for stronger research studies and toward personalised medicine to improve their quality of life.